Life During the Covid-19 Pandemic, From an Economic and Health Point of View - Abdul Rauf; Dhea Zatira; Metha Dwi Aprianti; Nining Purwaningsih; Lisdewi Mulyati (MOVE: Journal of Community Service and Engagement, 2021)
Seminar on Life in the Covid-19 Pandemic Period, in terms of economy and health is an activity to provide knowledge and descriptions of the covid-19 virus and the use of the family economy in improving welfare. The purpose of carrying out this activity is to provide understanding and knowledge about the covid-19 virus, sharing with doctors and the health team of Rs. Hermina Bitung, Providing training in utilizing the family economy and Providing training on introduction to financial management for families and family financial planning.